Analysis of needs for the development of BIPA teaching materials: Listening skills - Merlin Yupitasari; Diah Latifah; H. Halimah (Inovasi Kurikulum, 2024)
The development of Indonesian language teaching materials requires the application of technology to make it easier for students to receive lessons. This research analyzes the need to develop teaching materials for Indonesian listening skills for foreign speakers (BIPA). The research method used is quantitative with a descriptive approach. Data was collected by filling out questionnaires by 10 BIPA teachers from various institutions and observing relevant teaching manuals. The analysis results show that most respondents have taught BIPA for over five years and use audio and video media in listening learning. They stated that they needed interactive listening media and used materials from the institutions where they taught more often, even though they found several areas for improvement in the quality and suitability of the materials. Most respondents also expressed their readiness to be contacted further regarding this research. Data analysis also revealed respondents' preferences for using digital-based media to learn to listen to BIPA, with most respondents using platforms such as YouTube and Zoom Meet. These findings provide in-depth insight into teachers' preferences and needs in developing BIPA listening teaching materials and the importance of adapting learning materials to students' needs.